UPAYA DIGITALISASI GUNA PENGOPTIMALAN PENJUALAN PERINTIS KERIPIK PISANG RUMAHAN MELALUI REPACKAGING DAN PENGENALAN MARKET PLACE - Ade Ulul Azmi; Ruli Saefudin; Risna Zulfa Musriroh (FMIPA Unila, 2024)
MSMEs in Lumajang Regency, including banana chip producers, experienced a drastic decline following the COVID-19 pandemic. Bananas are a potential natural resource with superior varieties, namely Agung bananas and Kirana bananas. However, banana chips production has not utilized this potential optimally, causing inequality in the agricultural sector and food security. As a solution, community service has established partnerships with industry players who are able to guarantee the quality of banana chips. Mrs. Sulasmi, a small industry player was chosen to develop